Investasi Bandara Angkasa/Spaceport dalam Mewujudkan Indonesia sebagai Spacefaring Nation Studi Kasus Kerjasama Indonesia dan China - Yanuar Reza Wardana; Ika Riswanti Putranti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
This study aims to explain Indonesia in achieving its national interest in realizing security in the Spaceport Cooperation between Indonesia and China towards the efforts and attitudes of the Indonesian government in dealing with lagging behind in the field of space technology. Indonesia is currently facing problems in the development of space technology along with the development of globalization that is happening in the world. Indonesia seeks to overcome this, one of which is by cooperating with China in achieving the Space Renduk, where Indonesia currently still has to rely on countries that are superior in terms of mastering space technology. The author will use the concept of Space Power as a point of view in analyzing China's foreign policy using space technology capabilities, and Security Theory as Indonesia's strategy in achieving national interests in realizing security, as well as Foreign Policy Theory, as a strategy used in interacting to achieve its interests. This research tries to explain what factors made China agree to cooperate. In addition, this research will also present an analysis of the sustainability of this agreement, where this agreement is still running today.